Effect of farmyard manure, nitogen and source of fertilizer on growth, yield attributes and yield of indian mustard (Brassica juncea) - PATEL, R H; MEISHERI, T G (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during winter season of 1992-93 and 1993-94 at Agronomy Farm of the collegeat Anand, to study the effect of farmyard manure, N and source of fertilizer on growth, yield attributes and yield of indian mustard [Brassica juncea (L.) Czernj. & Cosson]. Plant height, and primary and secondary branches/plant increasedsignificantly on application of up to 10 tonnes/ha farmyard manure. Similarly, yield attributes, viz siliquea/plant, numberof seeds/siliqua, seed yield/plant, 1 000-seed weight, and the seed and stover yields improved significantly on farmyardmanure application. Its application @ 10 tonnes/ha was economical for yield and yield attributes. N @ 75 kg/ha significantly improved the yield parameters per plant such as siliquae, seed yield, number of seeds and 1 000-seed weight, and thereby the total seed yield of indian mustard also. A significant improvement in growth and yield attributes and the seed and stover yields was also noticed where S-containing feriilizers were applied compared with S-free source of fertilizers.